Leadership Styles and Effectiveness of Change - Kee, Swee Lin (2005)
This study assesses the relationship between leadership style and the effectiveness of change in organizations while taking into consideration the impact of individual’s resistance towards change on that relationship. The three leadership styles included were the participative, nurturant-task and autocratic style.